Seguimiento y observación del crecimiento agronómico en el cultivo del pepino (Cucumis Sativus L.) en el Ecuador - Espinoza Ronquillo, Samuel Ismael (2022)
This document deals with the monitoring and observation of agronomic growth in the cultivation of cucumber (Cucumis Sativus L.) in Ecuador. The proposed objectives were to monitor and observe the agronomic growth of the cucumber crop in Ecuador. Some cucumbers need to be grown in soil with good drainage and the ability to retain moisture. The soil must not be made and the pH must be between 5.8 and 6.6. Cucumbers are very sensitive to cold, plants and fruits can be damaged even by winter frosts. Currently, Ecuador has the largest cucumber production, which is carried out at 1,250 ha with a yield of 13.2 tm/ha, and it is the province of Guayas that leads the first place with 6,680 tm, but the yield of this vegetable in coastal areas it depends on the genetic material, climatic conditions and technological management of the crop. Reduce the planting of monocultures since it has been shown that they degrade the physical conditions of the soil and accelerate the erosion process.